Dynamics of dust clouds in plasmas - Kravchenko, O.Yu.; Yurchuk, M.M.; Radchenko, O.M. (Вопросы атомной науки и техники, 2007)
We study a dynamics of dust clouds embedded in the infinite uniform initially plasma using computer simulation. In the one dimension, the movement of dust particles and ions is governed by cold hydrodynamics equations, electrons are assumed to be in thermal equilibrium. It is assumed that the forces on the dust consist of electrostatic force and ion drag forces. The spatial distributions of parameters were obtained at various initial densities of dust grains at different times. Results show the expansion of dust clouds at low initial dust grain density, which is evidence of exceeding the electrostatic force over the ion drag force. At the increasing of dust density oscillations of the central part of dust cloud are observed.